Translation: Rights and Agency - A Public Policy Perspective for Knowledge, Technology and Globalization - Sadek, Gaafar (Université d'Ottawa / University of Ottawa, 2018)
Copyright law relegates translation to a secondary, or derivative, status, which means that publishing a translation requires the permission of the rights holder of the original. This thesis argues for the timeliness of revisiting the translation right by analyzing its foundations and its implications from a transdisciplinary public policy perspective. This is done by first studying the historical and philosophical foundations of copyright law itself where the translation right is housed, revealing questionable philosophical arguments and a colonial past that has created legal path dependencies. The thesis then undertakes an examination of the foundations of the translation right specifically, dubbed “the international issue par excellence,” which confirms the same pattern observed in the development of copyright law. Given the complete absence of the translator’s perspective from all international discussions on the translation right, copyright’s view of translation is then contrasted with recent scholarship in translation theory, with a special focus on the notion of agency(-ies), exposing the incompatibility of these views on translation, and highlighting the importance of including the perspective of translation studies in policies and laws related to translation. The last part of the thesis explores the present-day realities of knowledge societies, digital technologies, and globalization, in order to identify the role of translation today and in the future, while highlighting the tremendous gaps between the have’s and the have-not’s, and the necessity of recognizing the specificities of different societies. Knowledge is the new capital of the world, and the translation right is an impediment to the key role translation can potentially play in allowing societies to participate in the cycle of its consumption and regeneration. Digital technologies are powerful enablers that have allowed those who have leveraged and embraced them, such as the open movement and prosumers of all types, to transform the nature of their interactions with their environment macro- and microstructurally. This has also been reflected in the profession of translation, where collaborative projects are constantly initiated, while the nature of the translator’s work is changing to the point where one seriously doubts whether the provisions of the century-old translation right still apply to it. The discussion on globalization focuses on language in a globalized world, power relations between linguistic communities, and means of preserving linguistic diversity and heritage. The translation right, with its questionable foundations and outdated nature, is an impediment to the potential role of translation (as representative of the public interest) in the world, and must be revisited and at least reduced to the point of constituting balanced public policy. Social development, power relations and the necessity of differentiation (or “otherness”) are running themes throughout the work, which tries to balance between theoretical discussions from various relevant disciplines and reliance on United Nations and other public policy research.
Keywords: translation; copyright; intellectual property; knowledge society; digital economy; technology; globalization; translation theory; translation right; public policy; social policy; social development; international studies; agency; power; transdisciplinarity; metatheory; philosophy of law